PERANCANGAN KANTOR DINAS KOMUNIKASI DAN INFORMASI (KOMINFO) KOTA DENGAN PENDEKATAN ARSITEKTUR KONTEMPORER - Yusril A. Akili; Novita Shamin; Atrila Latinulu (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2025)
The Department of Communication and Information Technology (KOMINFO) is a local government agency that provides services in the fields of communication, information technology, cryptography, and statistics for the community. This agency is led by a Head of Department who is responsible to the Regent through the Regional Secretary. This study aims to design the KOMINFO office in Gorontalo City using a contemporary architectural approach. The selected location is in the East City District, Moodu Village. This redesign is motivated by the need for government facilities that support agency performance in the rapidly developing digital era. The application of contemporary architecture aims to create a functional, flexible, and aesthetically pleasing building that reflects KOMINFO's modern identity. Design characteristics include: dynamic geometric forms, environmentally friendly materials, wide openings for natural lighting, and adaptive spatial layout to accommodate advancements in information technology. This approach is expected to produce government facilities that are responsive to future advancements in communication and information technology.